2020
DOI: 10.3390/polym12081739
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mixing Method on Properties of Ethylene Vinyl Acetate Copolymer/Natural Rubber Thermoplastic Vulcanizates

Abstract: Thermoplastic vulcanizate (TPV) has excellent elastomeric properties and can be reprocessed multiple times. TPV is typically produced by using the dynamic vulcanization (DV) method in which rubber is crosslinked simultaneously with thermoplastics. Peroxide-crosslinked TPV can increase the compatibility between rubber and thermoplastics but loses its reprocessability due to excess crosslinking in the latter. In this work, we overcome this obstacle by using a two-step mixing method to prepare fully crosslinked e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…Only neat asphalt and PMAD0 exhibited smooth texture, while the PMAD0.5, PMAD1, and PMAD1.5 showed rough texture as can be seen in Figure 3 e,g,i, respectively. The TPV consisted of thermoplastic and crosslinked rubber particles, which could be observed by SEM ( Figure S3 ) from our previous work [ 33 ]. Therefore, the dispersion of TPV in PMA was observed in the fluorescence micrographs at 20× magnification.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Only neat asphalt and PMAD0 exhibited smooth texture, while the PMAD0.5, PMAD1, and PMAD1.5 showed rough texture as can be seen in Figure 3 e,g,i, respectively. The TPV consisted of thermoplastic and crosslinked rubber particles, which could be observed by SEM ( Figure S3 ) from our previous work [ 33 ]. Therefore, the dispersion of TPV in PMA was observed in the fluorescence micrographs at 20× magnification.…”
Section: Resultsmentioning
confidence: 94%
“…Thermoplastic vulcanizate (TPV) is a material that has been widely used owing to its excellent elastic properties from the rubber particles and can be recycled like thermoplastic by melting [ 31 , 32 ]. Our previous work [ 33 ] has explored the suitable method for preparing thermoplastic vulcanizate from natural rubber and ethylene vinyl acetate copolymer to be used as a package of solidified asphalt. The “Split-DV” method was recommended to prepare the material pair that can be crosslinked using peroxide crosslinking agent.…”
Section: Introductionmentioning
confidence: 99%
“…A very important thing analyzed in the research refers to the fact that the samples were obtained by depositing layers of rubber namely of PVC particles, which was not addressed in previous research when the rubber/PVC compositions were obtained by mixing the two components [16,22,25,40]. By adopting this method of obtaining the specimens, conditions have been created to establish the type of rubber (R2) to which the PVC particles adhere best.…”
Section: Determining the Structure Of Samples Materialsmentioning
confidence: 99%
“…Additionally, these results applied to other thermoplastics that could be crosslinked with peroxide, for example, polyethylene, polystyrene and polyvinyl alcohol. [22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to using polypropylene as the base resin, scholars have carried out other synthetic materials as base phase for TPVs research work. [31][32][33][34][35][36] Chatterjee et al 34 carried out researches on the preparation of TPVs maded by XNBR and PA12, and found that when the proportion XNBR to PA12 is 50:50, the blend shows the highest mechanical properties and superior thermal stability among all TPV samples. Kunanusont et al 35 prepared TPVs of ethylene vinyl acetate copolymer and natural rubber by using peroxide vulcanization and Chatterjee et al 36 studied the preparation and properties of silicone rubber/polyamide TPVs by dynamic vulcanization.…”
Section: Introductionmentioning
confidence: 99%